Management of Minor Head Injury - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1999)
A national sample of pediatricians, family physicians, and emergency physicians was surveyed by questionnaire regarding initial and subsequent management of minor head injury, and responses were analyzed at the University of Washington, Seattle; the American Academy of Pediatrics; the American Academy of Family Physicians; University of California; and Children's Hospital, Boston.